iBudaya: Indonesian Culture Portal based on Software as a Service (SaaS) - Winarno Winarno; Wella Wella; Rudy Pramono (Universitas Multimedia Nusantara, 2020)
The society of Indonesia faces problem of cultural crisis, especially the younger generation who prefer foreign culture rather than the local culture. This research aimed to find a way to conserve local culture by combining local culture with the development of information and communication technology. The method used in this study is content crowdsourcing because it requires the help of all society member to fill the content and data that will be managed later in large volumes. Therefore, it will use cloud computing, Software as a Service (SaaS). This research has successfully developed a portal called ibudaya that can accommodate cultural values and local wisdom in the form of multimedia content, such as in the format of video, pictures, pdf, Word, and Power Point. This research has successfully developed a portal that can accommodate cultural values and local wisdom in the form of multimedia content. The cultural portal can be accessed through the link address http://iBudaya.applikasi.online/. This portal will be further refined in terms of cultural content procurement, where the content is in the form of videos, pictures and folklore texts.